Influence of attitudes, enabling conditions and mediating effect of motivation on residents participation in the wetlands community of Sarawak, Malaysia - Johari, Shazali; Shah, Kaleem; Rosli, Zamri; Emang, Diana; Mariapan, Manohar; Kohdi, Muhammad; Alam, Mohammad Nurul (Forestry Department Peninsular Malaysia, 2023)
The National Ecotourism Plan of Malaysia 2016-2025 and the Kuching Wetlands National Park Assessment Plan 2010 have outlined the importance of community-based ecotourism activities. The role of the local community is crucial and the key to ensuring the success of ecotourism programmes. This study examines local community motivation as a mediating factor in the relationship between attitude, enabling conditions, and participation. The study applied the explanatory design and carried out the quantitative analysis of questionnaire survey data from 404 respondents using Smart-PLS version 3.2.9 and SPSS version 23. The results indicate that out of seven hypotheses developed in this study, five are accepted, while two hypotheses were rejected. The study further suggested that motivation partially mediates between attitude and participation, however, no mediating effect was observed between enabling conditions and participation. This study would contribute to the theoretical knowledge of the ecotourism sector and would be useful as empirical evidence for potential ecotourism initiatives in Kuching Wetlands National Park of Sarawak, Malaysia.